2005
DOI: 10.1177/107424840501000304
|View full text |Cite
|
Sign up to set email alerts
|

Tolvaptan Administration Does Not Affect Steady State Amiodarone Concentrations in Patients With Cardiac Arrhythmias

Abstract: Tolvaptan coadministration does not alter steady-state amiodarone or desethylamiodarone concentrations. Tolvaptan concentrations did not appear to be different from historical controls. The most frequently reported adverse event was polyuria (15 of 21 subjects for amiodarone + 30 mg tolvaptan); an expected outcome due to the known potent aquaretic action of tolvaptan. The combination of amiodarone and tolvaptan was well tolerated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 15 publications
(10 reference statements)
0
24
0
Order By: Relevance
“…Since it has become clear that tolvaptan is primarily metabolized via CYP3A4 [11], it was expected that racial differences in pharmacokinetic parameters would be minor for tolvaptan [12]. Therefore, we compared the pharmacokinetic data for Japanese subjects in present single-dose study with those reported by Shoaf et al, which mainly comprised Caucasian subjects (83%) [8].…”
Section: Pharmacokinetic Characteristicsmentioning
confidence: 84%
“…Since it has become clear that tolvaptan is primarily metabolized via CYP3A4 [11], it was expected that racial differences in pharmacokinetic parameters would be minor for tolvaptan [12]. Therefore, we compared the pharmacokinetic data for Japanese subjects in present single-dose study with those reported by Shoaf et al, which mainly comprised Caucasian subjects (83%) [8].…”
Section: Pharmacokinetic Characteristicsmentioning
confidence: 84%
“…Coadministration with ketoconazole increased maximal plasma concentration by 248% and the area under plasma concentration versus time curve by 440% [16]. Less than 1% of tolvaptan is excreted unchanged via the urine [16]. In a study evaluating the effect of tolvaptan 30 mg and 90 mg on amiodarone in otherwise healthy arrhythmia patients on chronic amiodarone therapy, tolvaptan did not affect amiodarone levels.…”
Section: Tolvaptan (Opc-41061)mentioning
confidence: 97%
“…Tolvaptan is primarily eliminated by CYP3A4. Coadministration with ketoconazole increased maximal plasma concentration by 248% and the area under plasma concentration versus time curve by 440% [16]. Less than 1% of tolvaptan is excreted unchanged via the urine [16].…”
Section: Tolvaptan (Opc-41061)mentioning
confidence: 98%
See 1 more Smart Citation
“…Less than 1% of the substance is eliminated unchanged via the urine [42]. In human, increases in tolvaptan concentrations (C max ) were less than doseproportional and plateaued at doses greater than 240 mg [43].…”
Section: R Antagonists Tolvaptanmentioning
confidence: 99%